Digital Logistics Agility: Construct Development and Validation in the Context of Developing Economies - Andrina, Anak Agung Ayu Puty; Sutrisno, Timotius F. C. W.; Radianto, Wirawan E. D. (Universitas Brawijaya, Indonesia, 2025)
Global and digital disruptions have transformed how logistics systems operate, demanding greater responsiveness and adaptability. However, in developing countries like Indonesia, fragmented digital adoption and limited coordination hinder the realization of agile logistics capabilities. This quantitative study aims to develop and validate the construct of Digital Logistics Agility (DLA), reflecting the capability of logistics systems to respond and adapt effectively in digital environments. This study employed a six-phase quantitative process, including a literature review, expert validation, item construction, and the distribution of a large-scale survey to 190 supply chain managers in the Indonesian food and beverage industry. Construct development was conducted through exploratory factor analysis, followed by confirmatory factor analysis, to identify and confirm construct dimensionality and measurement validity. The EFA results identified four underlying dimensions comprising 13 valid constructs that collectively represent the core structure of the DLA construct. Subsequent CFA confirmed this factor structure, demonstrating high reliability, satisfactory convergent validity, and an acceptable overall model fit. DLA can serve as a robust framework to evaluate logistics agility in digitally transforming supply chains. This study introduces DLA as a novel, empirically validated construct that bridges digital capability and logistics agility, with practical relevance for emerging markets.